The dengue virus envelope protein induced PAI-1 gene expression via MEK/ERK pathways - Shyu, Huey-Wen; Lin, Yi-Ying; Chen, Lien-Cheng; Wang, Yi-Fen; Yeh, Trai-Ming; Su, Shu-Jem; Cheng, Wei-Cheng; Chen, Chang-Yu; Lin, Kuan-Hua; Chou, Miao-Chen (Thrombosis and Haemostasis, 2010)
Dengue virus (DV) infections cause mild dengue fever or severe life-threatening dengue haemorrhagic fever (DHF)/ dengue shock syndrome (DSS). DV-infected patients have high plasma concentrations of plasminogen activator inhibitor type I (PAI-1). However, the mechanism to cause haemorrhage in DV infections remains poorly understood. In this study, investigation was carried out on the purified recombinant domain III of the envelope glycoprotein of DV serotypes 2 (EIII) and the signalling pathways of EIII leading to PAI-1 gene expression were measured by RT-PCR, Western blot, and immunofluorescence stain. Reporter gene constructs containing serially 5’-deleted sequences of the proximal human PAI-1 promoter region were constructed and then transfected to Huh7 cells, a human hepatoma cell line, prior to EIII treatment. EIII increased the PAI-1 mRNA and protein levels in a dose-dependent manner in Huh7 cells. Results showed that U0126, an inhibitor of extracellular signal-regulated kinase (ERK) kinase (MEK), almost completely suppressed EIII-induced PAI-1 expression. The results suggest that the MEK/ERK signalling pathways mediate the EIII-dependent induction of PAI-1 gene expression via the proximal promoter region.
Keywords: Flaviviridae; dengue virus type 2; envelope glycoprotein domain III; plasminogen activator inhibitor type-1